Influence of mutual drag of light and heavy holes on conductivity of p-silicon and p-germanium - Boiko, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Conductivity of p-Si and p-Ge is considered for the two-band model with due regard for mutual drag of light and heavy holes. It is shown that for small and moderate temperatures this drag significantly diminishes the drift velocity of light holes and, as a result, the whole conductivity of crystal. The drag effect considered here appears also in the form of non-monotonous dependences of conductivity on temperature and carrier concentration.